Understanding indicator choice for the assessment of research, development, and demonstration financing of low-carbon energy technologies: Lessons from the Nordic countries - Jonas Sonnenschein (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Rapid decarbonization of whole countries requires additional research, development, and demonstration of low-carbon energy technologies. Governments support research, development, and demonstration in this area with various financing instruments. These instruments are frequently assessed by carrying out indicator-based evaluations. So far there is no standard set of indicators for this purpose. This study looks at research, development, and demonstration financing in the Nordic countries, which are frequently mentioned as leading countries with respect to eco-innovation. Different indicators are identified, selected, and analysed. The analysis of the indicator-based evaluation method includes the acceptance of an indicator, its ease of monitoring, and its robustness as assessment criteria. No indicator or set of indicators emerges as clearly superior from the analysis. Indicator choice is subject to trade-offs. This means in turn that there is room for directing evaluation results by choosing certain indicators over others. The study concludes by discussing potential policy implications of biases in indicator-based evaluation of low-carbon energy technologies research, development, and demonstration funding.
Keywords: O38; O48; Q42; Q55; 330; decarbonization; indicators; low-carbon energy technology; Nordic countries; policy evaluation; research development and demonstration